Mir-338-3p Increases the Sensitivity to Oxaliplatin via Reversing Epithelial-mesenchymal Transition in Hepatocellular Carcinoma Cells - Huang, Chuan; Huang, Zhenguang; Luo, Jun; Wu, Meiyi; Cai, Kaining; Zhao, Ruiqiang; Wen, Yan (Recent Patents on Anti-Cancer Drug Discovery, 2026)
<span class=
Keywords: OXA-resistance